Western Balkans-EU Relations between the USA, Russia and Turkey - Yağmur Yetimoğlu; Gökhan Akşemsettinoğlu (Međunarodni Problemi)
Driven by stability and security concerns stemming from the recent past, the European Union (EU) has decided to include the Western Balkans (WB) in its enlargement process. In the meantime, the United States of America (USA), Russia, and Turkey have become engaged in promoting the need for balance of power in the region, although their interests have been mutually conflicting. In fact, the USA has supported the policies of the EU towards the WB to consolidate Euro-Atlantic integration and to maintain its authority as a superpower on the eastern side of the Atlantic. Another major power, Russia, has sought to counterbalance both the EU and the USA in the region by leveraging its close relations with Serbia. On the other hand, a neighboring country in the region, Turkey, has adopted the policy of soft power and good neighborly policy towards the WB to strengthen relations with old partners, based on perception of shared culture, heritage and history. This article analyzes the diverging national interests of the USA, Russia, and Turkey in the context of the Normative Power Europe approach pertaining to the WB.